2000
DOI: 10.1128/jvi.74.4.1810-1814.2000
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of the Astrovirus Capsid

Abstract: To further characterize the nature of proteolytic processing of the astrovirus capsid, we infected Caco-2 cells with a high multiplicity of astrovirus without trypsin in the presence of 5 to 10% fetal calf serum. These infections were characterized by pulse-chase labeling with [35 S]methionine, electron microscopy, gel electrophoresis of purified viral particles, and analysis of infectivity of such particles with and without added trypsin. Pulse-chase experiments showed that the astrovirus capsid protein was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
4
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 28 publications
5
110
4
3
Order By: Relevance
“…Previously published SDS-PAGE gels show that the amount of VP34 present in infectious particles was comparable to that of VP27 and VP25 (10,12), indicating that most of the VP27 and VP25, although covalently independent, remain associated with the particle in a disordered manner. The loss of the connection of VP25 to the capsid shell, however, may allow VP25/VP27 spikes to wobble around, thus resulting in orientation disorder and their disappearance from the EM reconstruction on quasi-twofold axes.…”
Section: Resultsmentioning
confidence: 97%
“…Previously published SDS-PAGE gels show that the amount of VP34 present in infectious particles was comparable to that of VP27 and VP25 (10,12), indicating that most of the VP27 and VP25, although covalently independent, remain associated with the particle in a disordered manner. The loss of the connection of VP25 to the capsid shell, however, may allow VP25/VP27 spikes to wobble around, thus resulting in orientation disorder and their disappearance from the EM reconstruction on quasi-twofold axes.…”
Section: Resultsmentioning
confidence: 97%
“…All astrovirus genomes show a rather conserved frameshift slippery sequence between ORF1a and 1b Marczinke et al, 1994), ensuring that the latter is only translated as a fusion polyprotein together with ORF1a, with an efficiency of 25-28 % when compared to the translation of ORF1a alone (Lewis & Matsui, 1996). The products from all three ORFs are posttranslationally cleaved into mature proteins (Bass & Qiu, 2000;Geigenmüller et al, 2002a;Gibson et al, 1998;Kiang & Matsui, 2002;Willcocks et al, 1999). However, the above information is derived mainly from studies with human astroviruses and similar data about animal astroviruses are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The products from all three ORFs are posttranslationally cleaved into mature proteins The GenBank accession number of the sequence reported in this paper is AY179509. (Bass & Qiu, 2000; Geigenmüller et al, 2002a;Gibson et al, 1998;Kiang & Matsui, 2002;Willcocks et al, 1999). However, the above information is derived mainly from studies with human astroviruses and similar data about animal astroviruses are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…By sequence comparison of HAstVs, the capsid protein precursor can be divided into a highly conserved N-terminal domain (aa 1-424), a hypervariable domain (HVR) (aa 425-688) and a highly acidic C-terminal domain (Wang et al, 2001). The mature infectious virion contains three predominant protein species derived from the N-terminal domain and from the HVR after intra-and extra-cellular processing (Bass and Qiu, 2000;Sanchez-Fauquier et al, 1994). Mapping of neutralising monoclonal antibodies (Sanchez-Fauquier et al, 1994) and structural analysis have revealed that AstV capsid spike is formed by dimerisation of a polypeptide spanning the HVR and a putative binding receptor site with affinity for polysaccharide molecules has been predicted in the spike structure (Dong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%